Bimetallic AgPd/UiO-66 Hybrid Catalysts for Propylene Glycol Oxidation into Lactic Acid - Ten, Sergey (Materials (Basel), 2020)
Different methods (the wetness impregnation of Ag and Pd precursors dissolved in water or acetonitrile solution, and the double solvent impregnation technique) were employed to immobilize Ag–Pd nanoparticles (NPs) into the pores of the microporous zirconium-based metal-organic framework known as UiO-66. The obtained materials were characterized by using nitrogen adsorption-desorption at −196 °C, powder X-ray diffraction, UV-Vis diffusion reflectance spectroscopy, and transition electron microscopy measurements. Special attention was paid to the acid and redox properties of the obtained materials, which were studied by using temperature-programmed desorption of ammonia (TPD-NH(3)) and temperature-programmed reduction (TPR-H(2)) methods. The use of a drying procedure prior to reduction was found to result in metallic NPs which, most likely, formed on the external surface and were larger than corresponding voids of the metal-organic framework. The formation of Ag–Pd alloy or monometallic Ag and Pd depended on the nature of both metal precursors and the impregnation solvent used. Catalytic activity of the AgPd/UiO-66 materials in propylene glycol oxidation was found to be a result of synergistic interaction between the components in AgPd alloyed NPs immobilized in the pore space and on the external surface of UiO-66. The key factor for consistent transformation of propylene glycol into lactic acid was the proximity between redox and acid-base species.